2021
DOI: 10.1186/s41016-021-00250-4
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA SNHG12 is a potential diagnostic and prognostic biomarker in various tumors

Abstract: Background Tumors are the second most common cause of death in humans worldwide, second only to cardiovascular and cerebrovascular diseases. Although methods and techniques for the treatment of tumors continue to improve, the effect is not satisfactory. These may lack effective therapeutic targets. This study aimed to evaluate the value of SNHG12 as a biomarker in the prognosis and clinical characteristics of various cancer patients. Methods We ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Accumulating evidence suggested that lncRNAs not only participated in the occurrence and development of many diseases [ 28 ] but also participated in the regulation of gene expression and immune response [ 30 31 ]. In addition, research on the use of lncRNA as a prognostic marker is increasing in various tumors including nasopharyngeal carcinoma, gastric cancer, hepatocellular cancer, colorectal cancer, breast cancer, and cervical cancer [ 32 ]. Therefore, it is necessary to explore the expression level of lncRNAs in diseases and their clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggested that lncRNAs not only participated in the occurrence and development of many diseases [ 28 ] but also participated in the regulation of gene expression and immune response [ 30 31 ]. In addition, research on the use of lncRNA as a prognostic marker is increasing in various tumors including nasopharyngeal carcinoma, gastric cancer, hepatocellular cancer, colorectal cancer, breast cancer, and cervical cancer [ 32 ]. Therefore, it is necessary to explore the expression level of lncRNAs in diseases and their clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, SOX5 upregulated the expression of oncogene Gelsolin and SNHG12, thus forming a positive feedback loop of SNHG12/miR-195/SOX5 [ 89 ]. Recently, SNHG12 has been recognized as a potential biomarker since its expression correlated with clinical characteristics and prognosis in various cancers, but also as a potential therapeutic target due to its involvement in the unfolded protein response-adaptive pro-survival mechanism exploited by many cancer cells [ 100 , 101 ].…”
Section: Lncrnas Acting Through Sox Genes In Gliob...mentioning
confidence: 99%
“…Activation of SNHG7 is associated with proliferation, tumor growth, migration, and invasion of BC cells by sponging miR-451a through inhibiting AKT/mTOR [40]. There is increasing evidence that altered SNHG7 expression may play a role in various malignant tumors [41]. SNHG7 upregulation in the cytoplasm also significantly increased Matrix Metallopeptidase 13 (MMP13) expression, whereas SNHG7 knockdown significantly inhibited MMP13 expression [42].…”
Section: Snhg12mentioning
confidence: 99%